Bowel preparation for small bowel capsule endoscopy - The later, the better! - Xavier, S. (2019)
In small bowel capsule endoscopy (SBCE), the presence of residue may compromise diagnostic accuracy. Background In small bowel capsule endoscopy (SBCE), the presence of residue may compromise diagnostic accuracy. Aims To assess differences in quality of visualisation and diagnostic yield of SBCE using 3 different preparation protocols. Methods Prospective, randomized, blind, pilot study. Protocol A:Clear liquids diet the day before the examination with fasting from 8p.m.; Protocol B:Protocol A + 2 pouches of Moviprep®(polyethylene glycol electrolyte solution + sodium ascorbate) in 1 L of water from 8p.m. of the day before the examination; Protocol C: Protocol A + 2 pouches of Moviprep® in 1 L of water consumed after real-time confirmation of capsule arrival at small bowel. Small bowel preparation was classified by two experienced physicians, considering the percentage of the examination during which mucosal observation was adequate: Excellent(>90%); Good(90–75%); Fair(75–50%); Poor(<50%). Results 101 patients randomized to the 3 protocols (A 37, B 31, C 33 patients). Protocol C had an excellent/good small bowel preparation in a higher percentage of examinations for both readers(Reader 1-A:37.8% vs B:45.2% vs C:78.8%, p = 0.002 and Reader 2 –A:37.8% vs B:41.9% vs C:75.8%, p = 0.003). Also, protocol C had a higher detection of angioectasia (A:5.4% vs B:9.7% vs C:27.3%, p = 0.022). Conclusions The administration of Moviprep® after the capsule had reached the small bowel was associated with a better small bowel preparation and a higher detection of angioectasia.